Forced migratory flows in Eastern Africa A preliminary analysis of refugees' reception in Ethiopia (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
In 1996, Gaim Kibreab referred to the African refugees as what the eyes refuse to see. Looking at the huge population shift from rural areas to the Eastern African cities, Kibreab observed that this population displacement was taking place in the absence of any structural transformation in the economies concerned. At that time African host-governments saw the situation in their urban centers being exacerbated by the presence of refugees who were said to compete with nationals for limited employment opportunities and social services. Less than twenty years later the situation is far from improved. Today, in the general context of the mixed migratory flows originating and transiting through the East Africa and the Horn of Africa region, refugee flows continue to represent a serious concern, with countries in the region simultaneously hosting and assisting internally displaced persons, refugees, returnees and labour migrants.